Pengendalian Risiko Keselamatan dan Kesehatan Kerja (K3) dengan Metode Failure Mode and Effect Analysis (FMEA) pada Eksploitasi dan Fine Gold Refinery Process (99,00%) di Koperasi Tombang Tujauh Loge, Riau - Sugiono, Nana; Surya, Roberta Zulfhi; Andivas, Marulan; Alpiyandri, Alpiyandri (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Tombang Tujuah Loge ASGM Cooperative operates in the field of Artisanal small-scale gold mining (ASGM) and produces fine gold. The Exploitation and Fine Gold Refinery Process involves direct interaction of workers with equipment and the environment in a production situation that has quite a high safety risk. The research aims to identify the type or source of danger, determine the high-risk value, and take appropriate risk control measures. The method used is Failure Mode and Effect Analysis (FMEA) to identify failures in facilities, systems, or equipment that have an impact on work accidents. The research results show that the highest risk is the danger of landslides at mining sites (RPN: 120) and exposure to dangerous chemicals in Fine Gold Refinery Process activities (RPN: 112). The results of data processing using Failure Mode and Effect Analysis (FMEA) provide recommendations, namely (1) Landslide Early Detection System; (2) Incinerator; and (3) Use of Personal Protective Equipment.